THE EFFECT OF CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE WITH INCENTIVES AS A MODERATING VARIABLE - Teguh Setiawan Wibowo; RA Retno Wulansari. K; Degdo Suprayitno; Thresia Winarti; Juni Iswanto (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is quantitative research with an exploratory approach, namely research that uses previous research as the main source for finding novelty in the research carried out. Of course, these studies are closely related to Career Development, Employee Performance and Incentives. This research uses primary data or data obtained from objects directly using a digital questionnaire instrument to obtain them. The digital questionnaire contains 5 choices of strongly agree, agree, neutral/average, strongly disagree, disagree, and so on for 300 CFC employees spread throughout Indonesia. Researchers analyzed these data using the smart PLS 4.0 analysis tool. The result in this research show the Career Development variable has a positive relationship and a significant influence on the Employee Performance variable because the P-Values results are positive and are below the 0.05 significance level, namely 0.008. The researcher's assumption, as stated in the questionnaire, is that employee career development that continues to improve can make the vision and targets given by the company easier to achieve. In the end, research on employee performance also increased. Apart from that, in the second row of the third table the path coefficient also shows that the second hypothesis in the research can also be proven if the Incentive variable can strengthen the influence of the Career Development variable on Employee Performance. This is due to the more incentives the company gives to employees, the more enthusiastic the employees will be at work, the more focused they will be at work, and in the end it can increase career development and improve employee performance. Based on these results, the first and second hypotheses in this research can be proven. Keywords: Career Development, Employee Performance ,Incentives